2020
DOI: 10.1021/acs.jpcc.0c04062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Confinement on the Dynamics and H-Bonding Pattern in Low-Molecular Weight Poly(propylene glycols)

Abstract: Herein, we explored thermal properties, dynamics, wettability, and Hbonding pattern in various poly(propylene glycols) (PPG) of M n = 400 g/mol confined into two types of nanoporous templates: silica (d = 4 nm) and alumina (d = 18 nm). Unexpectedly, it was found that the mobility of the interfacial layer and the depression of the glass transition temperature weakly depend on the pore size, surface functionalization, and wettability. However, interestingly, we have reported strengthening of the hydrogen bonds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…For all those materials, we can observe two endothermic signals discussed in the literature as a so-called double glass transition (DGT) phenomenon where both T g values are located above and below the one observed for the bulk material independent of the molecular weight of PhAs and pore diameters (see Figure b,c and Figure f,g). One can recall that similar findings are commonly reported in the literature for various glass formers under confinement, ,, including materials able to create excessive hydrogen bonding structures. According to the “two-layer” (or “core-shell”) model, , there are different types of interactions within infiltrated materials, which result in heterogeneity in terms of molecular dynamics as well as packing density .…”
Section: Resultssupporting
confidence: 83%
“…For all those materials, we can observe two endothermic signals discussed in the literature as a so-called double glass transition (DGT) phenomenon where both T g values are located above and below the one observed for the bulk material independent of the molecular weight of PhAs and pore diameters (see Figure b,c and Figure f,g). One can recall that similar findings are commonly reported in the literature for various glass formers under confinement, ,, including materials able to create excessive hydrogen bonding structures. According to the “two-layer” (or “core-shell”) model, , there are different types of interactions within infiltrated materials, which result in heterogeneity in terms of molecular dynamics as well as packing density .…”
Section: Resultssupporting
confidence: 83%
“…This finding indicates the occurring of an additional third glass transition temperature of unknown origin (labeled as T g,add ). In this context, one can recall some earlier works on poly(methyl methacrylate) (PMMA), 72 PPG, 63 and PMPS 71 confined within AAO porous templates, reporting the existence of the third T g , located between T g,core and T g,interfacial upon different heating/cooling rates due to the formation of the intermediate layer between the adsorbed and core molecules. 72 However, in our case, the additional T g, add is located far above T g,interfacial , suggesting a different origin of this anomalous glass transition temperature.…”
Section: Resultsmentioning
confidence: 91%
“…Since recent studies on various low- and high- molecular weight glass formers infiltrated into AAO templates have indicated that the structural/segmental dynamics strongly depends on the thermal history of the confined sample, we decided to explore this effect on spatially restricted PROa compound that is characterized by one of the highest pressure coefficient of the glass transition temperature, d T g /d p = 427 K/GPa. For that purpose, dielectric measurements on the confined API were performed using two different temperature protocols described in detail in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this paper, we focused exclusively on the analysis of the α-process. It is also worth adding that in the case of incorporated CLN, there was no sign of the “interfacial process” related to the reorientational motions of the molecules adsorbed at the surface of the pore walls, reported in the literature for various glass formers infiltrated into porous membranes (especially silica ones). Herein, it should be stressed that the presence or absence of this mode depends on many factors, for example, the time scale of the mass exchange between interfacial and core molecules, and the experiment time . The lack of the interfacial process in the loss spectra of the examined compound can be related to the fact that the exchange between both fractions of molecules is slow with respect to the time of the experiment. , …”
Section: Introductionmentioning
confidence: 95%